Low incidence of left atrial delayed enhancement with MRI in patients with AF: a single-centre experience. Issue 1 (9th January 2017) - Bois, John P; Glockner, James; Young, Phillip M; Foley, Thomas A; Sheldon, Seth; Newman, Darrell B; Lin, Grace; Packer, Douglas L; Brady, Peter A
Abstract : Background: Atrial fibrillation (AF) is the most common sustained atrial arrhythmia. One potential target for ablation is left atrial (LA) scar (LAS) regions that may be the substrate for re-entry within the atria, thereby sustaining AF. Identification of LAS through LA delayed gadolinium enhancement (LADE) with MRI has been proposed. Objectives: We sought to evaluate LADE in patients referred for catheter ablation of AF. Methods: Prospective analysis was conducted of consecutive patients who underwent pulmonary vein antrum isolation (PVAI) ablation for AF at a single institution. Patients underwent LADE with MRI to determine LAS regions before ablation. MRI data were analysed independently in accordance with prespecified institutional protocol by two staff cardiac radiologists to whom patient outcomes were masked, and reports of LADE were documented. Where no initial consensus occurred regarding delayed enhancement (DE), a third staff cardiac radiologist independently reviewed the case and had the deciding vote. Results: Of the 149 consecutive patients (mean (SD) age, 59 (9) years), AF was persistent in 64 (43%) and paroxysmal in 85 (57%); 45 (30%) had prior ablation. Only five patients (3%) had identifiable DE in LA walls (persistent AF, n=1; paroxysmal AF, n=4). LADE was present in two (4%) of the 45 patients with previous left PVAI. The presence of LADE was not associated with a higher recurrence rate of AF. Conclusions: In contrast to previous studies, the finding of DE within LA walls was uncommon and, when present, did not correlate with AF type or risk of AF recurrence. It therefore is of unclear clinical significance.